Acute and chronic effects of inspiratory muscle training in patients with type 2 diabetes mellitus: a systematic review of randomized controlled trials - Breuil-Marsal, Zoé; Godek, Clémence; Lotti, Amandine; Feiereisen, Patrick; Marçal, Isabela Roque; Rehder-Santos, Patricia; Milan-Mattos, Juliana Cristina; Abreu, Raphael Martins de (Frontiers in Sports and Active Living, 2024)
Objectives: To conduct a systematic review to determine the acute and chronic effects of inspiratory muscle training (IMT) in type 2 diabetes mellitus (T2DM) patients on cardiac autonomic function, glucose variability, inspiratory muscle strength and endurance, hemodynamic variables, and exercise capacity.Methods: A search was carried out according to a specific search strategy, following the PRISMA statement, and three independent reviewers have undertaken the article selection process. Searches were carried out in June 2023, on the following electronic databases: EMBASE, MEDLINE (PubMed), SCOPUS (Elsevier), and Web of Science. The methodological quality of the studies was assessed using the PEDro scale. The search was limited to English-language, randomized controlled trials (RCTs), involving T2DM patients (>18 years old, with or without autonomic neuropathy, and/or inspiratory muscle weakness) following an acute or chronic intervention protocol based on IMT. Exclusion criteria were reviews, clinical trials, case studies, theses, dissertations, scientific conference abstracts, subjects with other chronic respiratory/neurological/cardiovascular diseases, and studies addressing other breathing exercises.The search strategy identified 1,352 studies, of which eight (two involving acute and six involving chronic IMT effects) were included. A total of 214 adults aged 52-63 years (51/49 male/female ratio), with BMI ranging from 27 to 36.8 kg/m², were included. The results demonstrated that after IMT, acute effects were reported, such as reduced glucose levels and an increase in the parasympathetic pathway, but also chronic effects including improved inspiratory muscle strength, endurance, and exercise capacity.Although some methodological differences among the studies were found, IMT may have beneficial effects on cardiac autonomic function, glucose level control, inspiratory muscle strength/endurance as well as exercise capacity. However, further studies are necessary to confirm these benefits.